The Effectiveness of Learning Together in Teaching Writing at MA Ma'arif Al-Mukarrom - Wiranti, Nur Shofya; Agung, Winantu Kurnianingtyas Sri (Institut Agama Islam Negeri Ponorogo, 2025)
This research investigates whether there were differences in the results of students who taught using Learning Together and those who were not. Since writing is one of a language skill that difficult to master, but in fact this skill is tends to be ignored and only considered as part of grammar and syntax. Furthermore, to overview this research, quasi-experimental design was applied within XI grade students of MA Ma’arif Al-Mukarrom. To collecting the data, this study used a test and documentation. Meanwhile, the data analysis technique used normality test, homogeneity test and hypothesis test that calculated by SPSS 25. To test the hypothesis, the researcher used paired sample T-test. From the results of the paired sample t-test, a significance value of 0.000 was obtained. Therefore, the significance value is lower than 0.05 (0.000<0.05). So, it can be concluded that there are significant differences in students' writing skills between those who are taught using learning together and those who are not. Actually, LT is an effective strategy in teaching social subject lesson, by conducting this research proved that LT is appropriate strategy in language teaching.